Amplitude phase control for electro-hydraulic servo system based on normalized least-mean-square adaptive filtering algorithm - Yao, Jian-jun; Fu, Wei; Hu, Sheng-hai; Han, Jun-wei (Journal of Central South University, 2011)
The electro-hydraulic servo system was studied to cancel the amplitude attenuation and phase delay of its sinusoidal response, by developing a network using normalized least-mean-square (LMS) adaptive filtering algorithm. The command input was corrected by weights to generate the desired input for the algorithm, and the feedback was brought into the feedback correction, whose output was the weighted feedback. The weights of the normalized LMS adaptive filtering algorithm were updated on-line according to the estimation error between the desired input and the weighted feedback. Thus, the updated weights were copied to the input correction. The estimation error was forced to zero by the normalized LMS adaptive filtering algorithm such that the weighted feedback was equal to the desired input, making the feedback track the command. The above concept was used as a basis for the development of amplitude phase control. The method has good real-time performance without estimating the system model. The simulation and experiment results show that the proposed amplitude phase control can efficiently cancel the amplitude attenuation and phase delay with high precision.